Incarcerated Women: Need to Address Sexual Health. (1st August 2022) - Alshowaikh, K; Hutchinson-Colas, J; McGreevey, J; Bachmann, G
ABSTRACT: Introduction: Incarceration, which affects more than 200, 000 women annually, has a multidimensional negative impact on these women's health and wellbeing, including their sexual health. Sexual satisfaction, defined as a subjective evaluation of a sexual relationship, depends on several sociocultural and biopsychological factors, including the individual's physical and mental health, their schooling, and the intimacy setting. These factors are exacerbated in correctional facilities. Most obvious, is the women's lack of a desirable settings for sexual intimacy. It is essential to maintain sexual function in prison as women continue to be sexual beings with sexual needs. Despite this need, there are few initiatives addressing sexual health in incarcerated women, which is known to impact general and mental health, family function, and recidivism. The NJ Commission on Women's Reentry (NJCWR) was legislated to address the health and wellness of both incarcerated and reentry women, including their sexual health. Objective: To study incarcerated women's sexual health and the impact of incarceration. Methods: A Literature review was conducted on sexual function in US correctional facilities by searching PubMed/Medline and Google Scholar. Relevant publications were sought using keyword combinations including, "sexual function, " "sexual satisfaction, " "conjugate visits, " "incarcerated women, " "mental health, " "general health, " and "US correctional facilities." Results: Correctional facilities often enforce abstinence on incarcerated women and adopt deprivation as a measure to resolve sexual desires during incarceration. Additionally, limited knowledge is available about the quality of sexual experiences in the small number of facilities that provide conjugal visits. The available literature shows high levels of sexual dysfunction amongst incarcerated women that is significantly correlated with an increase in mental health issues, aggression, and recidivism. Data suggest that sexual deprivation is more significantly associated with mental health disorders than partner status and romantic relationships. Incarcerated individuals have expressed the lack of sexual contact as "sexual torture." Alternative methods sought may be coercive, less satisfactory, and/or riskier behaviors, possibly leading to transmission of sexual diseases. Only six states allow conjugal visits even though it is a suggested solution with primarily benefits including lower sexual offenses, rape, and disciplinary records in prison. However, many facilities that permit conjugal visits lack private space for the couple. Conclusions: Determinants of sexual health include complex cognitive, emotional, and physiological processes. Sexual deprivation and dysfunction dehumanize incarcerated women and negatively affect sexual health, in addition to overall general health. Sexual function and satisfaction is a primarily understudied area in the carceral system, considering all of the barriers to sexual expression. It is imperative for more initiatives, such as those being carried out by the NJCWR, in order to effectively address the needs of incarcerated women, including their sexual health. Disclosure: No